PENGARUH MODEL EXAMPLE NON EXAMPLE BERBANTUAN POWERPOINT TERHADAP HASIL BELAJAR DI SEKOLAH DASAR - Dwi Apriyani; Jayanti Jayanti; Ida Suryani (JS (JURNAL SEKOLAH), 2023)
Abstract: Using the utilization of PowerPoint, this study intends to ascertain how the example-non-example approach affects learning results at SD Negeri 34 Palembang. This study employed an experimental methodology and a control group design with pretest and posttests, a true experimental design. The sample size for this investigation was 55 people, consisting of class III.B as Class III, the the control class and the experimental class. totaled 27 students. The data analysis technique employed in this was the t-test investigation. According to the calculations and data analysisposttest results for the experimental class, the control class, and both averages were 64.07 and 64.07, respectively and 76.43. The findings of the t-test analysis demonstrate thatthe count value is more than the table value by 2.376. So, if Ho is turned down, Ha is. The resultant sig value is 0.021 0.05. Thus, the example non-example technique can be considered to exist, which was aided by PowerPoint, had a substantial impact on class III SD Negeri 34 Palembang students' learning of the properties of flat shapes in mathematics.Keywords: Mathematical example, non-example, and learning objectivesAbstrak: Penelitian ini bertujuan untuk menentukan bagaimana model contoh noncontoh berbantuan PowerPoint berdampak pada hasil belajar di SD Negeri 34 Palembang. Studi ini menggunakan desain eksperimen asli dengan desain kelompok kontrol pre-test-post-test. Dalam penelitian ini, sampel berjumlah 55 orang yang terdiri dari kelas IIIb sebagai kelas eksperimen berjumlah 28 siswa dan kelas III.a sebagai kelas kontrol berjumlah 27 siswa. Dalam penelitian ini, Nilai posttest kelas kontrol rata-rata 64,07 dan nilai posttest kelas eksperimen rata-rata 64,07. Hasil perhitungan analisis data adalah uji-t. dengan 76,43. Berdasarkan hasil analisis uji-t menunjukkan nilai thitung = 2,376 > ttabel = 1,674. Sehingga Ho ditolak berarti Ha diterima. Diperoleh nilai sig. sebesar 0,021 < 0,05. Dengan demikian Hasil belajar siswa kelas tentang materi bangun datar dan sifatnya III SD Negeri 34 Palembang dipengaruhi secara signifikan oleh model contoh non-contoh berbantuan PowerPoint. Kata Kunci: Example Non Example, Matematika, Hasil Belajar